Novel imaging biomarkers of response to transcatheter arterial chemoembolization in hepatocellular carcinoma patients - Favelier, Sylvain; Estivalet, Louis; Pottecher, Pierre; Loffroy, Romaric (Chinese Journal of Cancer Research; Vol 27, No 6 (December 22, 2015): Chinese Journal of Cancer Research, 2015)
Hepatocellular carcinoma (HCC) is the third most common cause of cancer death worldwide (1). Most patients present with intermediate or advanced disease that is not amenable to curative treatment, and the median survival in this group is 6-8 months (2). Several studies and well-designed randomized trials have shown a positive effect of transcatheter arterial chemoembolization (TACE) on patient outcome and survival (3-8). As nicely described in the present article from Wáng et al., assessment of tumor response is of extreme importance in patients undergoing locoregional treatments of liver cancer (9). Early assessment of the effectiveness of TACE and monitoring of tumor response are paramount to the identification of treatment failure, guidance of future therapy, and determination of the interval for repeat treatment. Wáng et al. confirm in this article that imaging evaluation of HCC response to therapy is generally and widely performed with cross-sectional imaging [computed tomography (CT) and magnetic resonance imaging (MRI)] by using the modified Response Evaluation Criteria in Solid Tumors (RECIST) criteria and the European Association for the Study of the Liver (EASL) criteria which have been introduced in the past decade (9). It is interesting to note that these criteria are not based on experimental or observational studies, but are proposed as revised versions of World Health Organization (WHO) and RECIST criteria (10-13). Initial reports showed that they were better than the latter for assessment of response, and both have been shown to be independent prognostic factors (14-19). Nevertheless, these criteria have been shown to have several limitations, mainly the lack of standardization, and there are concerns about applicability and reproducibility that have been raised. Indeed, they may be difficult to use, especially in heterogeneous lesions, and their use is dependent on operator experience. Although recent guidelines have acknowledged the potential value of these new criteria, they are not considered robust enough to replace older morphological criteria in trials (18). As a result, since they were first introduced, numerous studies have been published to better define the type and optimal number of target lesions, the ideal imaging technique, and the follow-up schedule. At present most teams perform one-dimensional mRECIST or two-dimensional EASL measurement of the enhanced portion of a maximum of two target lesions (18,19). Nevertheless, very recent data have suggested that three-dimensional (3D) evaluation of the whole tumor burden using specific software, functional imaging or cone-beam CT (CBCT) imaging may be of interest as novel imaging biomarkers to predict future tumor response to TACE in HCC patients (10,20-27).